Numerical solution of a PDE arising from prediction with expert advice - Jeff Calder; Nadejda Drenska; Drisana Mosaphir (European Journal of Applied Mathematics)
This work investigates the online machine learning problem of prediction with expert advice in an adversarial setting through numerical analysis of, and experiments with, a related partial differential equation. The problem is a repeated two-person game involving decision-making at each step informed by